Andrew Hodgson. The Post-War Experimental Novel: British and French Fiction, 1945-75. Bloomsbury Academic, 2020. - Kathryn Van Wert (Studies in 20th & 21st Century Literature, 2021)
Review of Andrew Hodgson. The Post-War Experimental Novel: British and French Fiction, 1945-75. Bloomsbury Academic, 2020. xi + 208 pp.
Keywords: post-war; experimental novel; Perec